Effectiveness of Application Behavioral Counseling Ivan Pavlov Lesson with Through Modeling Techniques to Improve Self Study Class X Mia Deference SMA Negeri 1 Denpasar - M.Razief dwi Alfian (RedwhitePress)
This study aims to Determine the effectiveness of Ivan Pavlov's behavioral counseling with modeling techniques through the LS method to improve self- deference, The sample of this study is classX MIA 1 Middle School 1 Denpasar, The collection of self- deferenceData in this study uses observations, questionnaires and diaries. So that it can be concluded that there is a high effectiveness in behavioral counseling Ivan Pavlov using modeling techniques in increasing the affiliation of students of classX MIA 1 Denpasar Middle School 1.